Design low elastic modulus Ti–Zr–Nb-Hf-Cu multi-principal element alloys for dental application - Zhichao Zhao; Bo Liu; Donghui Wang; Jing Jiang; Zhen Lu; Lei Yang (Journal of Materials Research and Technology)
Titanium and titanium alloys have been widely used as dental implant materials due to their excellent strength, stability, and biocompatibility. However, in clinical practice, the relatively high modulus of elasticity of titanium implants usually triggers the phenomenon of stress shielding, accompanied by the risk of post-implantation infection, which hinders the regeneration and reconstruction of bone tissue and may ultimately lead to implant failure. Multi-principal element alloys (MPEAs) offer enhanced control over the modulus due to their broad compositional variability. Herein, three MPEAs with the composition (TixZrxNbHf)95Cu5 (x = 2, 3, 4) were developed in this paper, which exhibits a lower modulus of elasticity contrast with TC4, and the addition of copper (Cu) is effective in suppressing post-implantation infection. These three MPEAs are primarily composed of body-centered cubic (BCC) structures and demonstrate excellent mechanical properties, including compressive plastic strain exceeding 40 %, yield strength up to 840 MPa, and a minimum elastic modulus of just 69 GPa, which is similar to that of human bone. Furthermore, the low elastic modulus MPEAs exhibit outstanding corrosion resistance in simulated body fluids, enhancing their durability under physiological conditions. In vitro cellular experiments confirm their excellent cytocompatibility and ability to promote angiogenesis, while in vitro bacterial studies demonstrate antimicrobial efficacy, with a rate exceeding the specified 90 %. In vivo experiments also further validated the osseointegration capacity. Incorporating copper into MPEAs with BCC structures presents a promising avenue for developing advanced dental implant materials.